2020
DOI: 10.3389/fmars.2020.00679
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Variability of the CO2 System in a Riverine Influenced Area of the Mediterranean Sea, the Northern Adriatic

Abstract: Coastal ecosystems are subject to multiple processes that drive pH change over time. Therefore, efforts to understand the variability in the coastal carbonate system are crucial to assess the marine system vulnerability to acidification. The variations of the carbon dioxide (CO 2 ) system were studied, from December 2014 to January 2017, on 6 stations along a transect latitudinally crossing the northern Adriatic, from the Po River delta to the Istrian Peninsula. The study aims to evaluate the influence of rive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 109 publications
0
15
0
3
Order By: Relevance
“…Following Urbini et al (2020), the North Adriatic Sea, due, probably to river discharges, shows pH values that decrease from West (8.4) to East (8.15), with pH measurements decreasing from the sea surface to the bottom, while, in detail, in the area of the Gulf of Trieste, in winter, pH values are higher (8.2) while in summer they are lower (7.9). During the velocity tests made with low-cost sensors, we measured a reference value with a top-end pH probe system.…”
Section: The Issue Of Precision Accuracy and Calibration Of Low-cost Sensorsmentioning
confidence: 98%
“…Following Urbini et al (2020), the North Adriatic Sea, due, probably to river discharges, shows pH values that decrease from West (8.4) to East (8.15), with pH measurements decreasing from the sea surface to the bottom, while, in detail, in the area of the Gulf of Trieste, in winter, pH values are higher (8.2) while in summer they are lower (7.9). During the velocity tests made with low-cost sensors, we measured a reference value with a top-end pH probe system.…”
Section: The Issue Of Precision Accuracy and Calibration Of Low-cost Sensorsmentioning
confidence: 98%
“…In a previous study undertaken at the Great Barrier Reef in northeast Australia, it was found that the CO 2 concentration was mainly controlled by temperature in the wet season (when the temperature was relatively high), while both temperature and other factors controlled the CO 2 concentration in the dry season (when the temperature was relatively low) (Lønborg et al, 2019). In the northern Adriatic Sea, Urbini et al (2020) found that temperature change was the dominant factor in summer, whereas the effect of biological processes was more dominant during other seasons. However, in August 2014, despite the high seawater temperature, the observed CO 2 concentrations were relatively low, the spatial variability was considerably large, and the pCO 2 results showed a significant deviation from the range of seasonal variability caused by temperature typically observed during the summer season in mid-latitude waters.…”
Section: Seasonal Variations Of Co 2 and The Influencing Factorsmentioning
confidence: 98%
“…14 Približno 60 % vnosa alkalnosti izvira iz Pada. 17 V severnem Jadranu alkalnost pada z naraščanjem slanosti 18 (slika 3). Vode Jadranskega morja so prenasičene glede na kalcit in aragonit v celem letu.…”
unclassified
“…Vpliv temperature (»termični«) na (izračunani) pCO 2 (pCO 2,NT ) prevladuje nad biološkim (»netermičnim«) vplivom (pCO 2,T ) (slika 6) v celotnem letnem obdobju v zalivu 16 , v severnem Jadranu pa je »termični« vpliv izrazit poleti in biološki vpliv prevladuje v ostalih sezonah. 18 Meritve pH v zalivu kažejo višje vrednosti pozimi in nižje poleti v plasti pri dnu (slika 7). Karbonatno ravnotežje v plasti pri dnu uravnavajo procesi na meji sediment-voda in v pornih vodah površinskega sedimenta.…”
unclassified
See 1 more Smart Citation